Oral fluid testing facilitates understanding of hepatitis A virus household transmission. (2019) - Haywood, Becky; Tedder, Richard S.; Beebeejaun, Kazim; Balogun, Koye; Mandal, Sema; Andrews, Nick; Ngui, Siew Lin
Abstract: The public health response to sporadic hepatitis A virus (HAV) infection, hepatitis A, can be complex especially when the index case is a child and no obvious source is identified. Identifying an infection source may avoid mass immunisation within schools when transmission is found to have occurred within the household. Screening of asymptomatic contacts via venepuncture can be challenging and unacceptable, as a result non-invasive methods may facilitate public health intervention. Enzyme-linked immunoassays were developed to detect HAV immunoglobulin M (IgM) and immunoglobulin G (IgG) in oral fluid (ORF). A validation panel of ORF samples from 30 confirmed acute HAV infections were all reactive for HAV IgM and IgG when tested. A panel of 40 ORF samples from persons known to have been uninfected were all unreactive. Two hundred and eighty household contacts of 72 index cases were screened by ORF to identify HAV transmission within the family and factors associated with household transmission. Almost half of households (35/72) revealed evidence of recent infection, which was significantly associated with the presence of children ⩽11 years of age (odds ratio 9.84, 95% confidence interval: 2.74–35.37). These HAV IgM and IgG immunoassays are easy to perform, rapid and sensitive and have been integrated into national guidance on the management of hepatitis A cases.